IMPLEMENTASI LANDASAN SPIRITUAL KEPEMIMPINAN KEPALA TK DALAM PEMBINAAN KARAKTER ANAK USIA DINI - Erni Erawati; Aslamiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early childhood character education is the main foundation for future personality development, but its implementation is often hampered by the lack of spiritual role models from institutional leaders. This article aims to analyze the implementation of the spiritual foundation of kindergarten principal leadership in developing early childhood character. The method used is a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. A literature search was conducted in Google Scholar, Scopus, and SINTA databases for the publication period 2015-2025. The initial identification process found 1,245 articles. After going through the screening stage based on the title and abstract, 85 articles remained. The eligibility stage by assessing the full text resulted in 32 articles that met the inclusion criteria. A total of 18 final articles were synthesized to answer the research objectives. The main findings indicate that the implementation of the spiritual foundation of kindergarten principal leadership is realized through exemplary religious values, the creation of a religious school culture, and the integration of prayers and moral stories in daily activities. Kindergarten principals act as role models who internalize honesty, empathy, and responsibility. The conclusion of this article confirms that the spiritual foundation of a kindergarten principal's leadership contributes significantly to the effectiveness of early childhood character development, but requires ongoing strengthening of the leader's spiritual capacity. Keywords: spiritual foundation, kindergarten principal, character education, early childhood